2017
DOI: 10.1103/physreva.96.013421
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling ionization of the F4 and D6 states of vanadium: Exchange blockade

Abstract: Using TDDFT calculations we compare tunneling ionization of the a 4 F ground state and the a 6 D first excited state of vanadium in laser fields of intensities between 1.4 and 4.0×10 13 W/cm 2 .The calculated ionization yields of the ground state of vanadium were already shown to agree well with experimental results [Chu and Groenenboom, Phys. Rev. A 94, 053417 (2016)]. We find that the tunneling ionization rate of the sextet state is lower than that of the quartet state. This is surprising, since the ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Another TDDFT study demonstrated the difference that the electronic structure can make in TI by comparing the ground state of vanadium [(3d 3 4s 2 ) 4 F ] to the (3d 4 4s) 6 D excited state. Even though the ionization potential of the 4 F quartet state is higher than that of the 6 D sextet state, the TI rates of the sextet turned out to be lower because of exchange blockade for the higher spin state [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another TDDFT study demonstrated the difference that the electronic structure can make in TI by comparing the ground state of vanadium [(3d 3 4s 2 ) 4 F ] to the (3d 4 4s) 6 D excited state. Even though the ionization potential of the 4 F quartet state is higher than that of the 6 D sextet state, the TI rates of the sextet turned out to be lower because of exchange blockade for the higher spin state [17].…”
Section: Introductionmentioning
confidence: 94%
“…We adopt an all-electron TDDFT method for treating openshell atoms. This approach was implemented for the neutralatom vanadium and explained its suppressed TI [15,17]. It is an optimized effective potential (OEP) formalism, which correctly accounts for the long-range exchange-correlation potential.…”
Section: Introductionmentioning
confidence: 99%
“…A TDDFT method with an optimized effective potential formalism was developed for studying the tunneling ionization of vanadium [19,25] and nickel [26]. In the TDDFT analysis, the ionization suppression of the neutral atoms and the enhancement of the cations were explained in terms of the AC Stark shifts, elevated tunneling barrier, exchange blockade, and the large centrifugal barrier for the d orbitals [26].…”
Section: Introductionmentioning
confidence: 99%